Partly cystic common peroneal nerve schwannoma: an unusual cause of hallux drop - Abhishek Mishra, MD; Naresh Kumar; Simarjeet Singh (The Journal of the International Society of Physical and Rehabilitation Medicine)
Traumatic peroneal nerve injury is the usual underlying cause for foot drop. Other causes are like neoplastic, metabolic, or infective are rarely seen. We are reporting an extremely rare case of peroneal neuropathy due to a partly cystic schwannoma of common peroneal nerve leading to hallux drop.